Potrait of Social Interaction among the Vilagers in the Perspective of George Herbet Mead’s Symbolic Interactionalism Theory - Ari Rohmawati; Meiwatizal Trihastuti; Anis Suryaningsih; Habib Ismail (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
The aim of this study was to know how the portrait of social interactions that occur between villagers in the Perspective of George Herbet Mead's symbolic intercationalism theory and to determine the factors that support social interaction between villagers. This article was descriptive qualitative. The researchers used documentation, observation and interviews in collecting the data. The result show that The form of social interaction that occurs between Restu Buana villagers and Bumi Nabung Ilir village residents is in the form of associative-cooperation (in the form of trade / buying and selling between villagers, friendship)/ Second, it is in the form of associative-accommodation (that is, in the event of a fight, usually with mediation by leaders religious. Third, the form of dissociation f-Contravention which is manifested by the feeling of resentment. Fourth, which is in the form of dissociative-competition such as competition in the economy. Factors that support social interaction: first, there is mutual tolerance between residents. Thirdly their mutual appreciation of cultures of other villagers. Keywords: Social Interaction, Symbolic Interactionalism Theory, Goerge Herbet Mead’s Symbolic